2017
DOI: 10.5604/01.3001.0010.3795
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemerin in human disease

Abstract: Adipose tissue is not merely a storage depot of triacylglycerols but also a major endocrine organ. Its cells, including adipocytes, synthesize and secrete a range of biologically active molecules termed adipokines. Adipokines that display the properties of cytokines are often called adipocytokines. In recent years there has been increasing interest in a new adipokine called chemerin. Chemerin is a protein synthesized mostly by the adipose tissue and the liver as inactive pre-pro-chemerin. After the intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…As is currently well known, adipose tissue itself represents an endocrine organ [29][30][31][32]. Recent studies have shown that obesity and the increase in the size and number of adipocytes are associated with an alteration of lipid and carbohydrate metabolism [31,33,34], insulin resistance and systemic inflammation [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As is currently well known, adipose tissue itself represents an endocrine organ [29][30][31][32]. Recent studies have shown that obesity and the increase in the size and number of adipocytes are associated with an alteration of lipid and carbohydrate metabolism [31,33,34], insulin resistance and systemic inflammation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue causes these changes through the secretion of biologically active molecules: over 600 adipokines (such as leptin, resistin, apelin, vaspin, omentin, visfatin, adiponectin, chemerin, etc. ), cytokines, both pro-inflammatory and anti-inflammatory, interleukins-IL (IL1, IL6), chemokines (IL8, MCP 1-monocye chemoattractant protein-1), vasoactive substances, interferon, and hormone-like action proteins [29][30][31][32][33][34][35]. The increase in the level of proatherogenic substances, with a pro-inflammatory effect, might trigger a cascade of insulin resistance [34], as well as the relationship between obesity and diabetes and vascular complications, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only CMKLR1 appears to be critical for chemerin-induced inflammation (Mariani and Roncucci, 2015). Chemerin binding to GPR1 produces only a weak effect in modulating calcium mobilization, while CCRL2 does not activate downstream signaling cascades (Stojek, 2017). In contrast, CMKLR1 has been reported to mediate chemerin-promoted inflammation in diabetic complication (Neves et al, 2018a,b;Zou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Its gene termed retinoic acid receptor responder 2 (tazarotene-induced gene 2) encodes for chemerin protein which is associated with obesity and inflammatory diseases (Bozaoglu et al, 2007). Chemerin receptors are expressed in the liver which proved that chemerin may be relevant in liver physiology and pathophysiology (Stojek, 2017). Chemerin has a chimeric nature; having pro-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%